AS REDES DA DIÁSPORA HAITIANA: UM ESTUDO SOBRE ACRISEIMIGRATÓRIA DOS HAITIANOS NO MUNICÍPIODE CORUMBÁ/MS-BRASIL NO PERÍODO DE 2017/2018 - PRISCILA SOUZA BARBOSA (2023)
Migration is a fundamental human right recognized by international humanrightsstandards, thus all human beings have the right to leave any country, including their own, and has the right to return to their country. This is essential to protect individual freedom, human dignity and the ability to pursue better life opportunities. Haitian immigrationinBrazil began with the political and economic instability faced in Haiti. The countryisoften cited due to political conflicts, economic crises and natural disasters in particular; Since 2010, Haiti has been hit by a devastating earthquake, with its epicenter near thecapital Port-au-Prince, resulting in widespread destruction. Since then, immigrationintoBrazilian territory has intensified, mainly in the south and southeast regions, suchasCorumbá. Given this context, the objective of this research was to analyze the Haitianimmigration crisis that occurred between 2017 and 2018, in the municipalityof Corumbá/MS. For this, a qualitative research of the bibliographical and documental review type was carried out, with searches in books, studies and legal documents that address the theme of this study. Haitian immigration in Brazil emerges amid the political and economic instability that plagues Haiti. The country frequently figures intheheadlines due to political conflicts, economic crises and natural disasters, notablythedevastating earthquake that shook the country in 2010, resulting in widespreaddestruction. From that moment on, the migratory flow to the Brazilian territoryintensified, notably in the south and southeast regions, including Corumbá. It is observedthat the processes of mobility and border crossing are intrinsically related to the migrationpolicies adopted by the countries of destination and transit of Haitian migrants. Thesepolicies play a significant role in shaping migratory movements, directly influencingtheway in which migrants access territories and the rights conferred on them.